Pemberlakuan Sanksi Cambuk, Qanun Jinayat di Aceh dalam Perspektif Hak Asasi Manusia - Ida Ayu Rosida; Achmad Hariri (Media of Law and Sharia, 2023)
The Province of the Special Region of Aceh is one of the special regions that has special autonomy in managing its area, this is in line with Law Number 11 of 2006 concerning the Government of Aceh. The term regional regulation of Aceh province which regulates the governance and life of the people of Aceh is called Qanun, the qanun itself contains Islamic sharia rules which have adapted to become Acehnese customs. This article was compiled to find out how the application of caning sanctions in the Aceh Qanun Number 6 of 2014 concerning Jinayat Law in the perspective of human rights. This study uses a normative legal method with a statute approach which refers to the concept of law as a rule and also uses legal doctrines which are then analyzed qualitatively and described in a descriptive form so that conformity is found between the subject matter and the normative provisions. Given that Aceh Province is a strong adherent of the Islamic religion, everything related to the life of its people must be based on Islamic law, especially in matters of criminal behavior.So the Aceh government with all its specificity in carrying out Islamic shari'ah made a regional regulation which was ratified in 2014, namely Aceh Qanun Number 6 of 2014 concerning Jinayat Law.